2013
DOI: 10.1002/qj.2220
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of short‐term probabilistic blending in different weather regimes

Abstract: This study explores the potential of regime‐dependent approaches to improve short‐range precipitation forecasts. Probabilistic forecasts have been generated from the radar nowcaster Radar Tracking and Monitoring (Rad‐TRAM) and the convection‐permitting weather prediction model of the Consortium for Small‐scale Modeling, Deutscher Wetterdienst (COSMO‐DE) using the neighbourhood method for a 99 day period during summer 2009. The convective adjustment time‐scale was used to classify the days of the investigated p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 38 publications
0
25
0
Order By: Relevance
“…A blending of nowcasts based on extrapolated radar data with probabilistic high resolution forecasts for precipitation forecasts has already been used by, for example, Kober (), Kober et al . (, ) and Scheufele et al . ().…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A blending of nowcasts based on extrapolated radar data with probabilistic high resolution forecasts for precipitation forecasts has already been used by, for example, Kober (), Kober et al . (, ) and Scheufele et al . ().…”
Section: Methodsmentioning
confidence: 99%
“…A blending of nowcasts based on extrapolated radar data with probabilistic high resolution forecasts for precipitation forecasts has already been used by, for example, Kober (2010), Kober et al (2012Kober et al ( , 2014 and Scheufele et al (2014). The UK Met Office combines extrapolated radar data with downscaled NWPs to their nowcasting tool called STEPS (Bowler et al, 2006).…”
Section: Blending With Deterministic and Probabilistic Forecastsmentioning
confidence: 99%
“…In the equilibrium regime the generation of CAPE is balanced by widespread convective heating associated with synoptic forcing, while in the non-equilibrium regime CAPE can rise to larger values since convection is limited by high convection inhibition (CIN) and its initiation is associated with local circulations in the boundary layer (weak large-scale forcing). Values between 3 and 12 h can be used as a threshold to discriminate between these regimes with a value of 6 h mostly used (Molini et al, 2011;Keil et al, 2014;Kober et al, 2014). Following Zimmer et al (2011), Tau is computed as…”
Section: Convective Adjustment Time-scale Computation (Tau)mentioning
confidence: 99%
“…The measure of the convective adjustment time‐scale τ has already been successfully applied to examine ensemble bias and spread of precipitation (Done et al. , 2006, 2011; Keil and Craig, 2011), to assess the length of impact of radar data assimilation in COSMO‐DE (Craig et al , 2012), to distinguish the skill of probabilistic forecasts (Kober et al , 2013), to study severe precipitation events in the Mediterranean using re‐analysis data (Molini et al , 2011) and to classify observed summertime precipitation (Zimmer et al , 2011).…”
Section: The Convective Adjustment Time‐scale τmentioning
confidence: 99%